Drifts, resistances, arts in/through the Anthropocene - Guerra, Paula (Farol, 2024)
We are experiencing a trans-global process of instability that affects several areas of human and non-human social experience and action. Thus, when we think about a dynamic of deconstruction of the Anthropocene era, we are, in fact, favoring a more comprehensive understanding around processes of individual and collective identity (re)construction, including aspects such as ecofeminism, multidimensional ecosystems, migrations, colonialism and decolonial thought, climate change, extractivism, among others, surrounding a whole diversity of dynamics that have the arts as their most perennial and (re)founding focus of expression. The artistic drifts and resistances in/through the Anthropocene presented here result from the convergence, communication and exchange in the areas of sociology, anthropology, cultural economics, cultural studies, urban studies, artistic education, humanities, architecture, art history, among others.